A Preliminary Test of the Efficacy of Brief Self-Administered Behavioral Interventions for Rumination. Issue 4 (July 2022) - Wolitzky-Taylor, Kate; Breland, Haley; Ross, Jaclyn; Sewart, Amy
Rumination is theorized to be a cognitive avoidance process that is implicated in several manifestations of psychopathology. Few interventions directly target rumination as a core process maintaining emotional disorder symptoms. This pilot study compared the feasibility and preliminary efficacy of self-directed behavioral approaches for reducing rumination. Participants ( N  = 60) with elevations in rumination were randomized to 3 weeks of self-directed interventions: (a) scheduled rumination time; (b) a strategy combining mindfulness, shaping, and disengagement strategies; or (c) self-monitoring control. Both active treatment conditions outperformed self-monitoring control on post-treatment depression scores. Scheduled rumination time significantly outperformed the other two conditions on measures of rumination and worry. No between-group differences emerged on the secondary outcome (i.e., anxiety symptoms). Brief, self-directed, behavioral interventions targeting rumination are feasible and demonstrate preliminary efficacy. Scheduled rumination time shows moderate to large effects. The use of a small, non-treatment seeking sample was the primary limitation.